Jesus in the Talmud - Schäfer, Peter 1943- (Princeton, NJ [u.a.] Princeton Univ. Press, 2007)
Jesus' family -- The son/disciple who turned out badly -- The frivolous disciple -- The Torah teacher -- Healing in the name of Jesus -- Jesus' execution -- Jesus' disciples -- Jesus' punishment in hell -- Jesus in the Talmud
Jesus' family -- The son/disciple who turned out badly -- The frivolous disciple -- The Torah teacher -- Healing in the name of Jesus -- Jesus' execution -- Jesus' disciples -- Jesus' punishment in hell -- Jesus in the Talmud
Includes bibliographical references (p. [191]-201) and index
Archivierung/Langzeitarchivierung gewährleistet
Keywords: Jesus Christ -- Jewish interpretations; Jesus Christ -- Jewish interpretations; Talmud -- Criticism, interpretation, etc; Bible -- Controversial literature -- History and criticism; Talmud -- Criticism, interpretation, etc; Bible -- Controversial literature -- History and criticism; Rabbinical literature -- History and criticism; Rabbinical literature -- History and criticism